Recent Sediment Analysis, Study Case: Sub Bottom Profiler Data Line 8 Geomarine Research Vessels - Ulil Amri (Journal of Wetlands Environmental Management, 2019)
North Aru Island’s offshore had a long exploration history since 1973 until present. The characteristics of seabed can be studied through the shapes, acoustic reflection pattern, type of substrate or sediment, or by living organisms at the seafloor. In Indonesia, the sub-bottom profiler data was previously only used to measure sea depth. This study was expected to provide overview and updated information about sea depth, seabed and sedimentary layers characteristics based on generated acoustical reflection values and to identify information about abiotic compounding seabed (grain size) used methods Folk 1974 and Spread. Resulted bathymetry data could explain the depth and topography of study areas, seabed characteristics, sea bed sediment classification that were expected to support the determination of shipping tracked lines, underwater pipelines construction, and to determine mineral compounds in the deep sea. The obtained data of field records were in digital *.odc format that is a standard format for BATHY-2010 software. In order to simplify data processing, there would be a series data conversion process into other formats. Data processing of sub-bottom profiling was conducted by Kogeo-imaging software. For more clear and better look than the playback data, the processing data was undergone some steps of treatments such as filtering, stacking and additional gain. Moreover, those data were interpreted at once time with digitizing to interpreted sediment layers. The sea depth of research location was around 52.59-97.03 below the sea surface. Sea bottom formed land (flat) was in the eastern part of the location. Steep basin or Aru Trough was in the western with type substrate of gravelly mud. In general, recorded seismic cut (section) was in the time domain which created vertical velocity distortion and lateral that would produce seismic records that would be different with its actual. Seismic only enabled to detect lithology border if there any acoustical impedance exchange which would be bigger than detectable limit of used seismic waves.